The quality of local governance and development under decentralization in the Philippines - Joseph J. Capuno (University of the Philippines, School of Economics (UPSE), 2005)
This paper attempts to trace and find evidence for the linkages between the quality of governance, and development at the local level since the adoption of the fiscal decentralization policy in the Philippines in 1991. The concern since then over the links has been prompted by the observed persistent imbalances in local development - across and within regions - which many believe is due to the less than prudent exercise of the devolved powers and responsibilities - hence, low quality of local governance. To be sure, the decentralization has led to not a few innovations in local service delivery and financing, and in increased people's participation in local civic activities. However, the spread of innovation has been slow and there has been less than genuine participation in the mandated local special bodies. The uneven quality of local governance thus may have contributed to imbalanced regional growth. Evidence also indicate that the initial level of economic conditions determine the acceptable quality of local governance, which explains why certain poor areas remain in the vicious circle of penury and misgovernance. To help improve the quality of local governance, some policy inputs are suggested.
Keywords: 330; Kommunale Selbstverwaltung; Dezentralisierung; Entwicklung; Philippinen; Good Governance